Analysis of different irrigants and irrigation protocols in cleaning, dentinal structure, and antibiofilm action - Borges, Mariana Maciel Batista (2022)
The aim of the first study was to investigate the biofilm response of two bacterial species after irrigation with 2% and 5% NaOCl mixed with HEDP for a prolonged period and under continuous flow. The increase in NaOCl concentration resulted in increased removal and disruption of the biofilm, as well as increased bubble formation. Association with HEDP caused a delay in the action of the hypochlorite, but without compromising the efficacy of the solution. In the second study, the influence of ethylenediaminetetraacetic acid (EDTA) pH on smear layer removal, effects on dentin structure, and antimicrobial action was analyzed. Regarding the removal of smear layer, there was no statistically significant difference between 17% EDTA pH5, pH7, and pH10. With respect to demineralization, acidified EDTA caused a higher and faster increase in the amide II/phosphate ratio. EDTA pH 7 showed a significant antimicrobial action and, in relation to its effect on the dentin structure, after irrigation with NaOCl, the amide II/phosphate ratio returned to the proportion close to the natural one. In the third study, the effect of different agitation protocols of the 2.5% NaOCl irrigating solution, associated or not with HEDP, on temperature was analyzed. Teeth were divided into 4 groups: G1 (NaOCl+Passive Ultrasonic Irrigation (PUI)), G2 (NaOCl/HEDP + PUI), G3 (NaOCl + Easy Clean (EC)) and G4 (NaOCl/HEDP + EC). At the end of the activation, the temperature (t) was measured and compared with t. initial. The cleaning of the dentinal tubules was analyzed using a Scanning Electron Microscope. PUI gently heated the different solutions, Easy Clean had the opposite effect. The association of NaOCl with chelating solutions promoted tubule cleaning.